‘Violence is completely normal’: Managing Violence Through Narrative Normalization - Storm-Mathisen, Frøja (The British journal of criminology, 2025)
This article introduces the concept ‘narrative normalization of violence’ as a theoretical framework for exploring the interplay between crime and marginality in street culture. Drawing from 4 months of ethnographic observations and 24 qualitative interviews with young men involved in a violent street culture in Oslo, Norway, the study identifies three prevalent narratives. The first, ‘Part of the game’, minimizes the danger of violence; the second, ‘It’s all about respect’, internalizes violence as part of a desired subcultural identity; and the third, ‘We come from concrete’, emphasizes the importance of belonging. In distinctive and important ways these narratives shape collective energies that influence beliefs, attitudes and aspirations, which work to narratively render the exceptional nature of violence manageable and mundane.